To Stem the Tide: Organizational Climate and the Locus of Knowledge Transfer - Di Stefano, Giada; Micheli, Maria Rita (Organization Science, 2023)
Prior work has maintained that organizations benefit from managing the transfer of proprietary knowledge. Transfer is often advantageous within organizational boundaries but may be harmful across them, because it might erode competitive advantage. Hence, we ask: How can organizations affect the direction in which knowledge flows? We examine the role of organizational climate as a governing mechanism for knowledge transfer. Our empirical strategy consists of a mixed-methods approach leveraging qualitative and experimental data over two cycles of theory building and theory testing. We start with an extensive field study of the European Organization for Nuclear Research (CERN), leveraging the insights from desk research, field observations, 53 interviews, and a laboratory-in-the-field experiment involving 518 physicists. We then provide a causal test of the emerging framework by means of two laboratory experiments with 389 participants. Our findings suggest employees are more likely to transfer knowledge to their colleagues when they identify as an integral part of the organization, but they would rather transfer knowledge to outside competitors when their organization encourages them to outperform coworkers. In the presence of an organizational climate that is unfavorable to preventing knowledge spillovers, we argue, organizations can redirect the locus of knowledge transfer internally by acting upon an individual employee’s job design and socialization regime. History: This paper has been accepted for the Organization Science Special Issue on Experiments in Organizational Theory. Funding: The authors acknowledge generous financial support from Bocconi University, the HEC Foundation of HEC Paris, and IESEG School of Management. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.1551 .